DEVELOPING MULTIMEDIA-BASED LISTENING MATERIALS FOR THE TENTH GRADE STUDENTS - Curnia Karim; Dyah Setyowati Ciptaningrum (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aimed at developing the supplementary multimedia-based listening materials for tenth grade students in the first semester using scientific approach Curriculum of 2013. This study was research development using the model by Brach (2009) and was conducted at MAN 1 Pamekasan. The final product of this study was in a macro-media flash file attached inside CDs. The result of the product evaluation and try-out showed that the materials were interestingly presented in terms of topics and listening activities. Moreover, it was also able to motivate students to learn listening.